The effectiveness of forgiveness therapy on emotional safety and aggression of correctional center adolescents - Moteabed, Maryam (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2021)
Background and Aim: Poor communication skills, undiagnosed physical problems, stress and frustration, patterning of behaviors with aggressiveness and observed violence, attracting the attention of friends, family or teachers, despair and doubt, lack of control of emotions, fear and lack of access to desires. Among the factors that can lead to aggressive behavior in teenagers are; Therefore, the present study was conducted to investigate the effectiveness of forgiveness therapy on emotional safety and aggression of juveniles in correctional centers. Methods: This research was a quasi-experimental study with a pre-test-post-test design with a control group. The statistical population of the research includes all teenagers of Tehran Correctional Center in 2021. The research sample consisted of 30 people (15 experimental people and 15 control people) of these teenagers, who were selected using the available sampling method and randomly divided into two experimental and control groups. The experimental group underwent remission therapy for 12 sessions, and the control group remained to wait for treatment during this period. Data collection was based on Casey Family Service Center Emotional Safety Questionnaire (2007) and Buss and Perry aggression scale (1992). The analysis of the information obtained from the implementation of the questionnaire was done through SPSS 23 software in the inferential section (analysis of covariance). Results: The research showed that forgiveness therapy is effective in correctional center teenagers’ emotional safety and aggression (P=0.05). Conclusion: The result of this research showed that forgiveness therapy leads to improvement of emotional safety and reduction of aggression in juveniles of correctional centers